Macedonian Constitutional Identity Versus “Ever Closer Union” Concept – Challenges, Dilemmas, and Perspectives - Karakamisheva-Jovanovska, Tanja (Maastricht 30: A Central European Perspective, 2025)
In the past 33 years of Macedonia’s independence, the country was involved in many economic, political, and inter-ethnic crises which were produced not only by internal, but also by external forces. Five of them have shaped the 33 years of political games and Macedonian struggles as an independent and sovereign country. From the non-recognition of its sovereignty through ethnic divisions to serious internal interferences by foreign ambassadors and mediators in the work of the domestic political institutions, Macedonia went through many heavy disruptions and challenges in the internal political reality and in the national and constitutional identity.The first major crisis happened in 1992 when Greece blocked Macedonia’s accession to full membership in the United Nations (UN), under its constitutional name Republic of Macedonia.The second crisis was triggered by the armed conflict in 2001. The public is still waiting for the answer to what kind of conflict it was. Was it a military conflict or a civil conflict with ethnic background? Was it a terrorist attack against a sovereign country and its independent institutions by armed forces which came from Kosovo, or was it a conflict for gaining more human rights, as the armed forces have claimed? The third serious political crisis happened at the end of 2014 and lasted very intensively in the following three years when the then opposition party, and now ruling party, publicly announced a massive scandal with illegal wiretapped conversations of then ruling politicians. The possession of recorded phone audio material by the opposition was announced after the failed meeting between the then leader of the opposition, later prime minister of the Macedonian Government, who tried to make the former Prime Minister into forming a technical government. What really made this political game so heated was not just the alleged seriousness of the illegal wiretapped materials which were in the opposition leader’s possession, but also the two parallel discourses which were formed around this issue that have completely polarized the Macedonian society.In the meantime, the fourth crisis occurred after the opposition took over the government, and after the Prespa Agreement was signed in 2018, which meant compulsory acceptance of the constitutional name change. This was done under very dubious circumstances when charges against MPs and their relatives were dropped so that the government could reach the two-thirds majority in the Parliament neededfor the name change. The Prespa Agreement did not only change the country’s name, but it also changed the constitutional and national identity and history. The goal of this agreement was not to put an end to the decade-long dispute opposed by Greece on Macedonia, but to make serious changes in the collective identity and the history of the Macedonian people. This Agreement seriously violated the international law, number of international human rights accords, which will be the subject of analysis of this paper.The fifth crisis happened in 2022 in correlation with the previous Bulgarian veto on the country’s EU accession talks. France presented a proposal for the resolution of the dispute between two the countries. The so-called French proposal contained an obligation of Macedonia to change its Constitution again and to acknowledge a Bulgarian minority in the constitutional Preamble as well as in other constitutionalprovisions. The French proposal was passed by the Bulgarian and Macedonian parliaments. Unfortunately, the truth is that with this French framework, nationalism is enshrined and it renders the country hostage to the whims and impulses of Sofia. Bulgaria wants to change the Macedonian identity, abusing the EU accession process and imposing its own distorted version of history. This version infringes not only Macedonian history, but also the history of the EU, including its anti-fascist roots. Many Western analysts underestimate this issue, without having sufficient background to properly judge what the stakes are. Unfortunately, the “Macedonian question” is as relevant again as it was in 1913.In the 21st century in the heart of Europe, two EU Member States abuse its position in the Union publicly denying Macedonia’s national and constitutional identity, making the acceptance of such denial from the Macedonian people as a condition for the start of negotiations with the EU. Keywords: politics, democracy, human rights, sovereignty, identity, crisis, international law, Constitution